IMPLEMENTASI SISTEM INFORMASI PERKEMBANGAN BALITA BERBASIS WEBSITE DI POSYANDU MELATI RW 2 KELURAHAN MUNJUL - Sri Lestari; Aryo Putra Ramadhan; Salsabila Putri Wibowo; Nicola Marthy (LPPM Institut Pendidikan Nusantara Global, 2025)
The development of toddlers is a crucial aspect of a child's growth, requiring regular monitoring to ensure each stage progresses properly. However, the recording of toddler development at Posyandu RW 2 Kelurahan Munjul is still conducted manually, making the process inefficient, prone to data loss, and time-consuming in reporting. To address this issue, a web-based toddler development information system was implemented to enhance the efficiency of data recording, management, and reporting of children's health information. The development of this system utilized the Waterfall model, which includes stages such as requirements analysis, system design, implementation, testing, deployment, and maintenance. The implementation results indicate that this web-based system accelerates the process of recording and processing toddler data, improves information accuracy, and facilitates access for healthcare workers and parents. Additionally, the system provides data visualization features in the form of graphs and digital reports, enabling a more effective analysis of toddler development. With this web-based information system, Posyandu RW 2 Kelurahan Munjul can improve the quality of health services for toddlers, optimize child growth monitoring, and expedite reporting to the Health Department. This system is expected to be adopted by other posyandu to support the digitalization of healthcare services through information technology.